Taking stock of South African accounting students’ pervasive skills development: Are we making progress? - Viviers, H A (South African Journal of Higher Education, 2016)
This study used a mixed-methods research design to take stock of the perceived level of awareness and perceived importance of pervasive skills development from three role-players in the South African accounting higher education environment, i.e. students, educators and employers. An investigation was launched into accounting students’ level of exposure to SAICA’s required pervasive skills set during their undergraduate studies. The results showed that students are aware of and perceive pervasive skills development as an important aspect of their higher education curricula. However, lacking emphasis was found in the development of leadership skills. Although educators are aware of their pervasive skills development responsibilities, its active incorporation into course modules is in need of improvement. Accounting employers want to be involved in pervasive skills development, especially in respect of team work and communication skills. Recommendations are made to enhance accounting education pedagogy in terms of pervasive skills development.